Gateway to dissent: the role of pro-Palestine activism in opposition to authoritarianism. Issue 7 (3rd October 2022) - Kurd, Dana El
ABSTRACT: Pro-Palestine activism in the Arab world has historically been one of the few tolerated avenues for political expression. Such activism is not an innocuous display of humanitarian concern for the plight of Palestinians, but rather a major driver of opposition to authoritarianism – particularly in highly repressive environments. In this article, I argue that pro-Palestine activism in the region has three impacts: 1) introducing activists in their formative years to the idea of political agency, 2) providing a space to engage in citizenship-building practices, and 3) generating spillover effects in the personal development of activists as well as in civil society more broadly. Using the case of Qatar and relying on 2 years of ethnographic fieldwork and interviews, I show how pro-Palestine activism consistently generated discussions and demands not only on the issue of Palestine, but on the idea of representative foreign policy, democratic decision-making, and the future of authoritarianism in Qatar, as well as in neighbouring Arab states. This sort of activism often goes unrecognized in the literature as a major driver of opposition, but is a crucial factor in our understanding of when and why dissent emerges in the region, even in environments when traditional civil society is nonexistent.